The gas chain: influence of its specificities on the liberalisation process - Carine Swartenbroekx (National Bank of Belgium, 2007)
Like other network industries, the European gas supply industry has been liberalised, along the lines of what has been done in the United Kingdom and the United States, by opening up to competition the upstream and downstream segments of essential transmission infrastructure. The aim of this first working paper is to draw attention to some of the stakes in the liberalisation of the gas market whose functioning cannot disregard the network infrastructure required to bring this fuel to the consumer, a feature it shares with the electricity market. However, gas also has the specific feature of being a primary energy source that must be transported from its point of extraction. Consequently, opening the upstream supply segment of the market to competition is not so obvious in the European context, because, contrary to the examples of the North American and British gas markets, these supply channels are largely in the hands of external suppliers and thus fall outside the scope of EU legislation on the liberalisation and organisation of the internal market in gas. Competition on the downstream gas supply segment must also adapt to the constraints imposed by access to the grid infrastructure, which, in the case of gas in Europe, goes hand in hand with the constraint of dependence on external suppliers. Hence the opening to competition of upstream and downstream markets is not "synchronous", a discrepancy which can weaken the impact of liberalisation. Moreover, the separation of activities necessary for ensuring free competition in some segments of the market is coupled with major changes in the way the gas chain operates, with the appearance of new markets, new price mechanisms and new intermediaries. Starting out from a situation where gas supply was in the hands of vertically-integrated operators, the new regulatory framework that has been set up must, on the one hand, ensure that competitive forces can be given free rein, and, on the other hand, that free and fair competition helps the gas chain to operate coherently, at lower cost and in the interests of consumers, for whom the stakes are high as natural gas is an important input for many industrial manufacturing processes, even a "commodity" almost of basic necessity.
Keywords: D23; D43; L13; L43; L95; L97; 330; network industries; gas industry; gas utility; liberalisation; regulation; deregulation; market structure; European gas supply; oligopoly; OPEG; Erdgasmarkt; Deregulierung; Regulierung; Energieversorgung; Unvollkommener Wettbewerb; Marktstruktur; Energiewirtschaft; EU-Staaten